RURAL DEVELOPMENT POLICY ON AREAS WITH NATURAL CONSTRAINTS IN THE REPUBLIC OF SERBIA - Papić, Ružica (Economics of Agriculture, 2022)
The aim of the research is to present the main challenges of Serbian agricultural policy towards areas with natural constraints in terms of delimitation, available measures and budgetary support. The methodological framework includes: descriptive statistics of areas with natural constraints, a qualitative analysis of strategic and programming documents and a quantitative analysis of budgetary transfers to agriculture. The results have revealed that a significant share of agricultural resources are concentrated in the areas with natural constraints, but, despite this fact, there is no specific measure for farms located in these areas. The implemented support measures are more oriented towards economic aspects, while other aspects such as promotion of sustainable farming practices and maintenance of the countryside are neglected. The Serbian policy towards areas with natural constraints needs to be more harmonized with the European policy (in terms of delimitation and support), and tailored to the specific needs of farmers in these areas.